Home sweat home : perspectives on housework and modern relationships - Patton, Elizabeth, 1975-; Choi, Mimi, 1963- (Rowman & Littlefield Publishers, 2014)
Coeditors Elizabeth Patton and Mimi Choi argue that an in-depth examination of media images of housework from the mid-nineteenth century to the early twenty-first century is long overdue. Modern depictions often imply that certain concerns can be resolved through excessive domesticity, reflecting some of the complicated and unfinished issues of second-wave feminism. Home Sweat Home: Perspectives on Housework and Modern Relationships reveals how widespread the cultural image of "perfect" housewives and the invisibility of household labor were in the past and remain today. In this collection of essays, contributors explore the construction of women as homemakers and the erasure of household labor from the middle-class home in popular representations of housework. They concentrate on such matters as the impact of second-wave feminism on families and gender relations; of popular culture--especially in film, television, magazines, and advertising--on our views of what constitutes home life and gender relations; and of changing views of sexuality and masculinity within the domestic sphere. Home Sweat Home will interest students and scholars of gender, cultural, media, and communication studies; sociology; and American history and appeal to anyone curious about housework, gender relations and popular culture